Crecimiento, progreso económico y emprendimiento - Miguel-Ángel Galindo Martín; María Teresa Méndez Picazo; María Soledad Casta\~no Martínez (Journal of Innovation & Knowledge (JIK), 2016)
Economists have traditionally been interest in analyzing economic growth enhancing factors. Entrepreneurship is one of factors considered by economists. However, in this analysis is also necessary to be considered how economic progress and distributive justice are affected. Usually economic growth and progress have been considered as synonymous, but following Holcombe (2007) it is possible to distinguish them since the former is related to the amount of product while economic progress is related to the quality of the product. This is important because some of the economic policy measures designed to promote economic growth can generate problems, for example, inequality. These problems could be solved, for example through a "compensation principle" to avoid that distributive justice and progress will be harmed. The aim of this article is to analyze these issues. We will begin considering the relationship between economic growth and progress in order to focus on the aspects of distributive justice and to design some economic policy measures to enhance economic growth and progress.
Keywords: E62; O40; 650; Growth; Progress; Entrepreneurship; Distributive justice; Compensation principle